The laser of the future: reality and expectations about the new thulium fiber laser—a systematic review - Kronenberg, Peter (Transl Androl Urol, 2019)
The Holmium:yttrium-aluminum-garnet (Ho:YAG) laser has been the gold-standard for laser lithotripsy over the last 20 years. However, recent reports about a new prototype thulium fiber laser (TFL) lithotripter have revealed impressive levels of performance. We therefore decided to systematically review the reality and expectations for this new TFL technology. This review was registered in the PROSPERO registry (CRD42019128695). A PubMed search was performed for papers including specific terms relevant to this systematic review published between the years 2015 and 2019, including already accepted but not yet published papers. Additionally, the medical sections of ScienceDirect, Wiley, SpringerLink, Mary Ann Liebert publishers, and Google Scholar were also searched for peer-reviewed abstract presentations. All relevant studies and data identified in the bibliographic search were selected, categorized, and summarized. The authors adhered to PRISMA guidelines for this review. The TFL emits laser radiation at a wavelength of 1,940 nm, and has an optical penetration depth in water about four-times shorter than the Ho:YAG laser. This results in four-times lower stone ablation thresholds, as well as lower tissue ablation thresholds. As the TFL uses electronically-modulated laser diodes, it offers the most comprehensive and flexible range of laser parameters among laser lithotripters, with pulse frequencies up to 2,200 Hz, very low to very high pulse energies (0.005–6 J), short to very long-pulse durations (200 µs up to 12 ms), and a total power level up to 55 W. The stone ablation efficiency is up to four-times that of the Ho:YAG laser for similar laser parameters, with associated implications for speed and operating time. When using dusting settings, the TFL outperforms the Ho:YAG laser in dust quantity and quality, producing much finer particles. Retropulsion is also significantly reduced and sometimes even absent with the TFL. The TFL can use small laser fibers (as small as 50 µm core), with resulting advantages in irrigation, scope deflection, retropulsion reduction, and (in)direct effects on accessibility, visibility, efficiency, and surgical time, as well as offering future miniaturization possibilities. Similar to the Ho:YAG laser, the TFL can also be used for soft tissue applications such as prostate enucleation (ThuFLEP). The TFL machine itself is seven times smaller and eight times lighter than a high-power Ho:YAG laser system, and consumes nine times less energy. Maintenance is expected to be very low due to the durability of its components. The safety profile is also better in many aspects, i.e., for patients, instruments, and surgeons. The advantages of the TFL over the Ho:YAG laser are simply too extensive to be ignored. The TFL appears to be a real alternative to the Ho:YAG laser and become a true game-changer in laser lithotripsy. Due to its novelty, further studies are needed to broaden our understanding of the TFL, and comprehend the full implications and benefits of this new technology, as well its limitations.